IMPROVING STUDENTS’ READING COMPREHENSION ON NARRATIVE TEXT THROUGH HERRINGBONE TECHNIQUE - Mardiyani, .; ., Apriliaswati; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract:This study isintendedto improve the students’ reading comprehension on narrative text, especially detail information, main idea and vocabulary through Herringbone technique. Herringbone is the technique to help students find important information and main idea in a text by seeking answer six comprehension questions on a diagram. Method of the research is a Classroom Action Research which is conducted in three cycles. The subject of this research is eleventh grade students, numbering 34 students. The data is collected by using observation checklist, fieldnote, and test. The data is analyzed by describing the observation checklist and fieldnote, and by using formula of mean score. The results indicate the students’ reading comprehension on narrative text improve in three cycles through Herringbone technique. Key words: Reading Comprehension, Narrative Text, Herringbone Technique, and Classroom Action Research. Abstrak: Penelitian ini dilaksanakan untukmeningkat kankemampuan siswa dalam memahami teks naratif khususnya, informasi yang detail, ide pokok dan kosa kata dengan menggunakan teknik Herringbone. Herringbone teknik adalah sebuah teknik untuk membantu siswa menemukan informasi penting dan ide pokok didalam sebuah teks dengan menjawab enam pertanyaan pemahaman pada sebuah diagram. Penelitian ini adalah sebuah penelitian tindakan kelas dalam tiga siklus. Subjek dari penelitian ini adalah kelas XI IPS, yang berjumlah 34 orang. Data penelitian dikumpul dengan melalui ceklis observasi, catatan lapangan dan tes evaluasi. Data tersebut dianalisa dengan mendeskipsikan ceklis obeservasi, catatan lapangan dan menggunakan rumus mencari nilai rata-rata siswa. Hasil penelitian menunjukan kemampuan siswa memahami teks naratif meningkat dalam tiga siklus dengan menggunakan teknik Herringbone. Kata Kunci: Pemahaman Membaca, Teks Naratif, Teknik Herringbone, dan Penelitian Tindakan Kelas.